To find the proportional relationship derived from the equation of the line y = mx, we need to first determine the value of m (the slope).
Given the two points (6,3) and (0,9), we can calculate the slope using the formula:
m = (y2 - y1) / (x2 - x1)
m = (3 - 9) / (6 - 0)
m = -6 / 6
m = -1
Therefore, the equation of the line is y = -x.
This means that the proportional relationship derived from this equation is that as y decreases by 1 unit, x will increase by 1 unit. This indicates a constant rate of change between x and y, affirming their proportional relationship.
the graph shows the proportional relationship derived the equation of the line y=mx thru the origin.(6,3) (0,9)
1 answer